Becoming what you want to be - Denise Batchelor (London Review of Education, 2006)
Challenges to become what you want to be permeate higher education recruitment literature, inviting students to realize their dreams. Students do not interpret this invitation only in vocational terms. Other aspects of meaning for being and becoming are important for them: self-realization, and becoming who as well as what they want to be. A student voice for being and becoming is less valued and validated in contemporary higher education, and more vulnerable, than voices for knowing and doing. Yet if voices for being and becoming are unsupported, voices for knowing and doing also become vulnerable. Integrity of voice is undermined.